Percutaneous dilatational tracheostomy compared to surgical tracheostomy for emergency medical patients requiring prolonged mechanical ventilation - Mandip Singh Bhatia; Amod Kumar Jaiswal; Navneet Sharma; Kirubakaran Kothandaraman; Sandeep Bansal; Saurabh C. Sharda (Muller Journal of Medical Sciences and Research)
Background and Objectives: Tracheostomy is a commonly performed procedure in critically ill patients requiring prolonged mechanical ventilation due to airway issues resulting from neurological, respiratory, and infectious diseases. This study aimed to compare the outcomes of percutaneous dilatational tracheostomy (PDT) with surgical tracheostomy (ST) in patients admitted to the emergency medical ward and requiring prolonged mechanical ventilation. The objectives were to evaluate and compare the two techniques, with respect to turnaround time, procedural time, incidence of surgical site infection, procedure-related bleeding, ventilator-associated pneumonia (VAP), and mortality. Methods: This prospective cohort study was conducted at the Division of Acute Care and Emergency Medicine, and the Department of Otolaryngology, Head and Neck Surgery, at the Postgraduate Institute of Medical Education and Research (PGIMER), Chandigarh. We enrolled adult patients (over 18 years), who required tracheostomy for long-term airway management (beyond 14 days). The patients were assigned to either the PDT or ST group by the attending physician. PDT was done at the bedside by emergency physicians using the Portex ULTRAperc single-stage dilator kit. ST was performed in the operating room by otolaryngology surgeons. Patients were followed up for 3 months, and efficacy and safety outcomes were compared between the two groups using Mann–Whitney U-test for nonparametric continuous data, while Chi-squared and Fisher’s exact tests were used for comparison of categorical data. Results: A total of 50 patients were enrolled in the study, with 25 patients each in the PDT and ST groups. The age and sex distribution, baseline Glasgow Coma Score, Sequential Organ Failure Assessment Score, indications for intubation, and comorbidities did not differ significantly between the two groups. The median (interquartile range [IQR]) turnaround time for PDT was 1 (1–1) day, significantly shorter than the 3 (2–4) days for ST (P < 0.001). Furthermore, the median (IQR) procedural time for PDT was 5 (4–6) min, significantly shorter than the 12 (10–14) min for ST (P < 0.001). PDT exhibited a lower rate of surgical site infections (n = 7) (28%) compared to ST (n = 15) (60%) (P = 0.023). Although the PDT group had two incidents of hemorrhage (n = 2) (8.0%), the difference compared to the ST group (n = 0) (0%) was not statistically significant (P = 0.49). The PDT group was comparable to the ST group with regard to incidence of VAP (13 vs. 13, P = 1.00) and 90-day mortality (14 vs. 15, P = 0.77). Conclusions: In critically ill patients requiring prolonged mechanical ventilation, the advantages of PDT included reduced turnaround and procedural times, as well as a significantly lower rate of surgical site infections. While PDT showed a slightly higher incidence of hemorrhage, both the PDT and ST groups had a similar incidence of VAP and mortality.